2012
DOI: 10.1007/s10750-012-1002-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of riparian forest disturbance on stream temperature, sedimentation, and morphology

Abstract: Forested headwater streams rely on their riparian areas for temperature regulation, woody debris inputs, and sediment retention. These products and services may be altered by disturbances such as timber harvest, windthrow, or development. This study investigated the effects of riparian forest disturbance by removing trees using 50 and 90% basal area harvests and by directly felling some trees into eight streams in eastern West Virginia. On summer afternoons, water temperature increased in the 50 and 90% BAH tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 61 publications
2
34
0
8
Order By: Relevance
“…Nevertheless, where urbanization, agriculture, or livestock grazing occurs, riparian forests are often cleared and are then succeeded by meadow or other herbaceous communities with a more open canopy. This alteration in riparian community can lead to major changes in stream ecosystem structure and function, including narrower and more embedded channels (because of encroachment by herbaceous plants), impaired ability to breakdown organic pollutants, changes in macroinvertebrate abundance, and higher water temperatures (Sweeney et al, 2004;Lecerf et al, 2012;Studinski et al, 2012). Recent studies have documented increases in stream temperature over large geographic areas in many parts of the world (Nelson and Palmer, 2007;Kaushal et al, 2010;Hester and Doyle, 2011) that have been attributed to climate change, human alterations of stream channels and hydrology, or a combination of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, where urbanization, agriculture, or livestock grazing occurs, riparian forests are often cleared and are then succeeded by meadow or other herbaceous communities with a more open canopy. This alteration in riparian community can lead to major changes in stream ecosystem structure and function, including narrower and more embedded channels (because of encroachment by herbaceous plants), impaired ability to breakdown organic pollutants, changes in macroinvertebrate abundance, and higher water temperatures (Sweeney et al, 2004;Lecerf et al, 2012;Studinski et al, 2012). Recent studies have documented increases in stream temperature over large geographic areas in many parts of the world (Nelson and Palmer, 2007;Kaushal et al, 2010;Hester and Doyle, 2011) that have been attributed to climate change, human alterations of stream channels and hydrology, or a combination of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Areas with higher slopes are more susceptible to soil erosion when compared to flat regions. Several studies report the importance of forest in fragile areas, such as riparian zones (Gregory et al 1991;Allan 2004;Studinski et al 2012). The presence of forest cover in such areas reduce risk of erosion and prevent landslides, stabilizing banks and preventing river siltation, owing to the forest deep and strong root system which promotes greater soil and water conservation compared to pasture and crops (FAO 2008).…”
Section: Local Demandmentioning
confidence: 99%
“…The effectiveness of the riparian vegetation has been supported by many studies over the recent past (Gregory et al 1991;Allan 2004;Studinski et al 2012). The reforestation of riparian corridors should be one of the priority actions to improve the quality of waterbodies (Wasson et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Over time, this can increase infiltration and decrease runoff, which is responsible for increased sediment yield in streams (Anderson and Lockaby, 2011). Although the interest in SBZ thinning is increasing in the Southern USA (Keim and Schoenholtz, 1999), few studies have observed the impacts of harvesting within SBZs on water quality and quantity within the region (Hodges, 2009;Lakel et al, 2010;Studinski et al, 2012;Kara et al, 2014) and the knowledge on the appropriate type of SBZ harvesting to minimize the effect of harvesting on water yield, water quality, and riparian values is limited (Prud'homme and Greis, 2009).…”
Section: Introductionmentioning
confidence: 99%